Village Institutional Transformation to Smart Village Governance in Tourism Village Development - Siti Anggraheni; Asep Nurjaman; Muhammad Kamil (Jurnal Public Policy, 2022)
Institutional transformation is one of the main keys to realizing Smart Village. A Smart village cannot be separated from technology, in realizing Smart Village there are several things that must be fulfilled, namely: institutions, resources, service chains, service delivery technologies, and mechanics. This research is qualitative research with a case study approach. The research location of Boonpring Ecotourism, Sanankerto Turen, Malang Regency. The research findings show that the Village Institutional Transformation towards Smart Village Governance is successful because the achievement of smart village governance in Sanankerto village is inseparable from the success of the institutional transformation carried out. This is shown by the success of developing tourism potential in the village. The village cooperates with several actors, namely: the government, universities, the private sector, local communities, and the media. It is hoped that sustainable smart village governance will be realized. This is inseparable from the participation and activity of the community who take a role in the development of tourist villages. The existence of smart village governance that is intertwined with the development of tourist villages in the Sanankerto village has succeeded in